Outsourcing Border Control Politics and Practice of Contracted Visa Policy in Morocco - Infantino, Federica; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
This book explores the everyday practices of border control and implementation of mobility policy in the European Schengen area by analyzing consular visas services on the edges of the territory. Using an original case study, private contractors that implement EU visa policy on governments' behalf, the author focuses on visa application centers located in Morocco and run by the two major contractors of European Member States, the transnational corporations VFSGlobal and TLSContact. The analysis builds on ethnographic research that encompasses the making of EU visa policy at the European, national and local levels. It aims at uncovering the reasons that have led to the adoption of outsourcing as a normal and legitimized mode to implement EU visa policy and the effects of that choice. .
1. Bordering Outside the State -- 2. Outsourcing in Practice -- 3. The Politics of Private-Public Cooperation.
Keywords: European Union; Europe-Politics and government; Migration; Comparative Politics; Public policy; Public administration